The production process and organization of the international cultural event: European Theatre Night in Bosnia and Herzegovina - Nezirović, Senada; Krdžalić, Denis; Žunić, Lejla (Journal for Geography, 2024)
The European Theatre Night is a one-day event that takes place every year in European countries, and since 2010, Bosnia and Herzegovina has also participated. The program includes theatre performances and other forms of performing arts. The European Theatre Night is the largest and most extensive theatrical manifestation and one of the most significant cultural manifestations in post-war Bosnia and Herzegovina. The work mainly deals with the analysis of this manifestation, that is, the main actors of the organization and cooperation, artistic institutions in which various theatre institutions, organizations and artists participate.